Effectiveness of TachoSil as Sealant in Lymphatic Leakage of Breast Cancer With Axillary Dissection - ArshadUllah Khan; Loai Albinsaad; Mohammed Alessa; Alghaydaa Fouad Aldoughan; Ammar Jaafar Alsalem; Noof Khalid Almukhaimar; Abdulrahman Ahmed Alghamdi; Watan Abdulla Alsahlawi; Batool Abdullah Alahmary (International Journal of Breast Cancer)
Conclusion: The findings suggest that TachoSil sealant effectively reduces early postoperative lymphatic drainage volume and maintains lower drainage rates up to 10 days following axillary dissection in breast cancer patients. The use of TachoSil sealant may have potential benefits in reducing the incidence of complications associated with lymphatic drainage and improving patient outcomes.